2013
DOI: 10.1002/cbf.2964
|View full text |Cite
|
Sign up to set email alerts
|

T‐LAK cell‐originated protein kinase is essential for the proliferation of hepatocellular carcinoma SMMC‐7721 cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide and typically has poor prognosis. Like most cancers, altered gene expression was always associated with the induction and maintenance of HCC. Here, we reported that the expression level of T-LAK cell-originated protein kinase (TOPK) is significantly up-regulated in human HCC samples and cell lines. The suppression of TOPK by short hairpin RNA in HCC cell line SMMC-7721 caused cell cycle arrest and reduced cell growth and colony for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…August 2014 cells, [12][13][14] and we found that TOPK was significantly activated by IPostC after 2-hour ischemia/1-hour reperfusion. We, therefore, hypothesized that (1) IPostC probably reverse the increases of oxidative stress within ischemic neural cells; (2) IPostC might activate TOPK that induce neural cells to express antioxidative molecules that would contribute to the neuroprotection of IPostC; and (3) the PTEN/Akt pathway is the downstream target of TOPK, all contributing to the neuroprotection of IPostC in vivo.…”
Section: Strokementioning
confidence: 68%
See 1 more Smart Citation
“…August 2014 cells, [12][13][14] and we found that TOPK was significantly activated by IPostC after 2-hour ischemia/1-hour reperfusion. We, therefore, hypothesized that (1) IPostC probably reverse the increases of oxidative stress within ischemic neural cells; (2) IPostC might activate TOPK that induce neural cells to express antioxidative molecules that would contribute to the neuroprotection of IPostC; and (3) the PTEN/Akt pathway is the downstream target of TOPK, all contributing to the neuroprotection of IPostC in vivo.…”
Section: Strokementioning
confidence: 68%
“…Evidence supports that the PTEN/Akt pathway is an important downstream target of TOPK in promoting the proliferation and migration of tumor cells. [12][13][14] One notion is that overexpression of TOPK decreases the expression of PTEN and increases the activation of Akt in lung cancer cell lines. 12 Another idea is that TOPK phosphorylates PTEN at the S380 residue and inactivates PTEN, which in turn activates Akt that leads to proper G2/M progression.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al reported that TOPK mRNA were highly expressed in bladder cancer and that TOPK protein was also detected in about 65% of patients with bladder cancer . Using fresh surgical specimens of hepatocellular carcinoma (HCC), Chen et al also found that HCC cells expressed TOPK mRNA and protein. Joel et al isolated glioma‐initiating cells (GICs) from surgical specimens and found that GICs expressed TOPK mRNA and protein …”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of TOPK as a novel MAPKK‐like protein kinase , further studies have been conducted with respect to downstream targets . TOPK has been reported to phosphorylate and inactivate PTEN, which in turn activates Akt, leading to proper G 2 /M progression in HeLa cells .…”
Section: Discussionmentioning
confidence: 99%